Recasting Commodity and Spectacle in the Indigenous Americas - Gilbert, Helen; Gleghorn, Charlotte (University of London Press, 2020)
Indigenous artists frequently voice concerns over the commodification of their cultures, a process acutely felt by those living with the consequences of colonialism. This timely book, which features color illustrations throughout, examines the ways in which contemporary indigenous peoples in different parts of the Americas have harnessed performance practices to resist imposed stereotypes and shape their own complex identities. Essays by leading academics and practitioners show the vibrancy of a wide array of indigenous arts and cultural events in the United States, Mexico, Peru, Bolivia, Canada, Nicaragua, Ecuador, and Belize. As well as analyzing performance idioms, the authors trace the circulation of creative products and practices as commodities, as cultural capital, and/or as heritage. Making reference to aesthetic forms, intellectual property, and political empowerment, these essays weigh the impact of music, festivities, film, photography, theater, and museum installations among diverse audiences and discuss ways in which spectacles of cultural difference are remodeled in the hands of indigenous practitioners.